Epidural esketamine and morphine for postoperative analgesia after caesarean delivery: A pilot study - Tang, Ju; Zheng, Zhiguo; Ran, Qijun; Zhao, Feng; Wang, Yao; Hu, Feng; Yang, Chao; Tan, Xiaoyong (Frontiers in Surgery, 2023)
Objective: The aim of this study was to determine whether the addition of esketamine to morphine would improve postoperative analgesia after caesarean section. Methods: Parturients who planned for a caesarean delivery using combined spinal-epidural anaesthesia with a request for postoperative anaesthesia were randomly divided into four groups (A, B, C and D). When the surgery was completed, the parturients in groups A, B, C and D were administered 2 mg morphine, 0.25mg/kg of esketamine, 0.25mg/kg of esketamine plus 2 mg morphine sulfate and 0.25mg/kg of esketamine plus 1 mg morphine through the epidural catheters, respectively. The postoperative pain at rest, pain with movement, the number of rescue analgesics and adverse effects were evaluated for 48 h after caesarean delivery. Results: A total of 119 parturients were included in this study, including 30 cases in group A, 30 cases in group B, 30 cases in group C and 29 cases in group D. All VAS scores at rest and with movement were much lower in group C as compared with those in group A and group B (P < 0.05). Besides, VAS scores at rest were also lower in Group C than in group D for 24 h (P < 0.05). Corresponding to the low pain scores, parturients in group C also required less rescue analgesia as compared with the other three groups (P = 0.021 for C vs A, P < 0.001 for C vs B and P < 0.001 for C vs D). There were no statistically significant differences between the four study groups as regards the incidence of adverse events (P > 0.05). Conclusions: The addition of esketamine to morphine improved postoperative analgesia after caesarean section without increasing the incidence of adverse events.